Association between fibroblast growth factor receptor 4 polymorphisms and risk of hepatocellular carcinoma - Yang, Yuan; Zhou, Yun; Lu, Ming; An, Yu; Li, Rui; Chen, Yao; Lu, Da-Ru; Jin, Li; Zhou, Wei-Ping; Qian, Ji; Wang, Hong-Yang (Molecular carcinogenesis, 2012)
Human fibroblast growth factor receptor 4 (FGFR4) polymorphisms have recently been shown to be associated with tumor progression of various types of cancer, including cancer of the breast, colon, and prostate and sarcoma. However, their association with hepatocellular carcinoma (HCC) is unknown. We evaluated the association of FGFR4 polymorphisms with risk of HCC in a study population with HCC and with/without hepatitis B virus (HBV) infection in East China. We genotyped four FGFR4 SNPs (rs351855, rs641101, rs376618, and rs31777) in 1,451 Chinese subjects, including 711 patients with HCC, 368 controls with HBV infection and 372 controls without HBV infection, using the TaqMan genotyping assay. Unconditional logistic regression analysis was performed to evaluate associations of genotypes of each SNP with HCC risk. For the rs351855 (Arg388) locus, we observed a reduced HCC risk associated with the T variant genotypes, particularly for those whose tumors with gross portal vein tumor thrombosis (gross PVTT) (OR = 0.66; 95% confidence interval, 95% CI = 0.46–0.95 for CT + TT). Such a protective effect was also observed for those with liver cirrhosis (OR = 0.42; 95% CI = 0.20–0.88 for CT + TT). Clearly the T allele was associated with these conditions. Our findings suggest that genetic polymorphism in FGFR4 may be a marker for risk of HCC with liver cirrhosis and gross PVTT in Chinese populations. © 2011 Wiley Periodicals, Inc.